Extensive cell heterogeneity during persistent infection with foot-and-mouth disease virus. - de la Torre, J C (1989)
Coevolution of viruses and the host cells occurred in BHK-21 cell cultures persistently infected with foot-and-mouth disease virus (FMDV) (J. C. de la Torre, E. Martínez-Salas, J. Diez, A. Villaverde, F. Gebauer, E. Rocha, M. Dávila, and E. Domingo, J. Virol. 62:2050-2058, 1988). In the present report we provide evidence of an extreme phenotypic heterogeneity of the cells, which was generated in the course of persistence. A total of 248 stable cell clones isolated from FMDV carrier cultures at early or late passages were analyzed. At least six distinct cell phenotypes were distinguished with regard to cell morphology, resistance to FMDV strain C-S8c1, and cell growth characteristics. No infectious FMDV or viral RNA was detected in variant cell clones, suggesting that the altered phenotypes were caused by inheritable cell modifications, selected in the course of persistence. Thus, the FMDV-BHK-21 carrier cell system must be described as a dynamic interaction between an evolving heterogeneous population of virus and multiple cell variants. We suggest that cell heterogeneity confers a selective advantage for long-term virus and cell survival by providing the cell population with a range of responses toward FMDV.